Teachers' and Prospective Teachers' Responses to Mentoring in the Creation of PMRI Learning Tools for Early Childhood Education Students - Efriani, Arvin; Asyfira, Intan Buhati; Rohman, Asep; Septy, Liana (Jurnal Sustainable, 2024)
This research aimed to describe the responses of teachers and prospective teachers regarding the mentoring in creating Indonesian Realistic Mathematics Education (PMRI) learning tools for early childhood education students using contexts from the surrounding environment. Environmental contexts were used in the learning process to understand concepts or learning materials more concretely. This was a qualitative descriptive research study. The data collection techniques used were explanations, question and answer sessions, and exercises. The result of this research was positive responses from teachers and prospective teachers based on the creation of PMRI learning tools for PAUD students using contexts from the surrounding environment.